INDEKS MASSA TUBUH - Rachel Dwi Wilujeng (Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: Early puberty in young women is marked by the arrival of the first menstruation called menarche. This can occur at the age of 9-13 years. From a preliminary survey at Walisongo Gempol Pasuruan Middle School, data from 10 female teenage respondents were found, 40% of girls experienced menarche at the age of> 13 years. The decrease in age in getting menarche is largely influenced by nutritional status that can be measured using the Body Mass Index. The purpose of this study was to determine the relationship between Body Mass Index and age of menarche in young women in Walisongo Gempol Pasuruan Middle School. Method: The research method used was cross sectional with a population of 8th and 9th grade research population totaling 232 students. Sampling was done by systematic random sampling and a sample of 45 students was obtained. Then the frequency table is made, cross tabulated and analyzed with the Spearman Rank Test. Results: The results showed that most of the girls had a BMI <18.5, namely 25 people (55.56%). Of the young women who had a BMI <18.5 who got menarche at age <13 years as many as 4 people (16.67%) and who got menarche at age> 13 as many as 21 people (84.0%). From the Spearman Rank Test results found that p (0.00) <? (0.05) then H0 is rejected, which means there is a relationship between BMI and age of menarche. Discussion: there is a relationship between BMI <18.5 with the age of menarche in young women. The higher the BMI value, the lower the age of menarche. So that treatment is needed to improve the health of adolescent girls, regarding monitoring nutritional status and education about adolescent health.